Cracking Behavior of Fiber-Reinforced Concrete Beams Made of Waste Sand - Jacek Domski; Joanna Laskowska-Bury; Anna Dudzińska (Applied Sciences)
This report presents the results of cracking tests on concrete beams. The test specimens were created in ten different series. Each series comprised two beams, six cylinders, and twelve cubic samples intended for the determination of strength properties. These samples varied in terms of the type of concrete mixture (fiber-reinforced fine aggregate concrete and plain concrete), the applied steel fibers (50/0.8 mm and 30/0.55 mm), the longitudinal reinforcement ratio in beams (0.6%, 0.9%, 1.3%, and 1.8%), and the inclusion (or exclusion) of compressed reinforcement and vertical stirrups. The fine aggregate concrete was made from waste sand, which is a byproduct of the hydroclassification process of gravel. The use of this sand in fiber concrete will help reduce the exploitation of natural resources and lower carbon dioxide emissions. Based on four-point beam bending tests, the study experimentally determined cracking moments, crack spacing, and crack width. Additionally, these results were compared with calculations proposed by L. Vandewalle and Domski, as well as with the methods outlined in Eurocode 2. The analyses conducted show that the best agreement between the research results and the calculations was obtained for Domski’s proposal. It follows that the average percentage error was 38.4%, indicating the safe use of this method.